European Institutions Acting Outside the EU Legal Order: The Impact of the Euro Crisis on the EU's 'Single Institutional Framework' - Flore Vanackère; Yuliya Kaspiarovich (European Papers, 2022)
(Series Information) European Papers - A Journal on Law and Integration, 2022 7(1), 481-506 | Article | (Table of Contents) I. Introduction. - II. The case of the ESM: why the Eurozone's governance does not question the unity of the EU institutional framework. - II.1. The establishment of the ESM. - II.2. The institutional functioning of the ESM. - III. The impact of tasks entrusted to the EU institutions under the ESM on the institutional equilibrium within the EU legal order. - III.1. How are new tasks entrusted to the EU institutions? - III.2. What impact do these new tasks produce on the institutional equilibrium within the EU? - IV. The post-Covid institutional set-up: back to a "community" mode of governance? - V. Conclusion. | (Abstract) In the aftermath of the global financial crisis, the EU and its Member States had to face very pragmatic issues: how to avoid the economic collapse of Greece, Portugal and Ireland? Decisions had to be taken quickly in any institutional or legal forum that was immediately available. For this specific reason, legal solutions entailing the conclusion of international agreements by some of the EU Member States outside the EU legal framework were taken as a new normal. Due to a close legal relationship between these new international treaties and the EU legal order, a decision was also taken to "borrow" already existing EU institutions and entrust them with new tasks. In this Article, we question the role of EU institutions outside the EU legal framework. We first address the evolution of the EU institutional framework in the context of the euro crisis in relation to art. 13 TEU and recital 7 of the TEU preamble and the requirement of "unity of the institutional framework". Section II shows that "borrowing" the EU institutions outside the EU legal framework does not seem to alter the nature of the single EU institutional setting. Section III questions whether the tasks entrusted to the EU institutions outside the EU legal framework do not undermine the existing institutional equilibrium within the EU legal order. Section IV addresses the EU response to the Covid-19 pandemic from an institutional perspective as raising similar concerns within the EU legal order. The last section concludes.